Robotic Assisted Laparoscopic Prostatectomy after High Intensity Focused Ultrasound Failure - Leon Telis; Seyed Behzad Jazayeri; David B. Samadi (Case Reports in Urology)
Background. Prostate cancer is the most common cancer diagnosed in men. As new focal therapies become more popular in treatment of prostate cancer, failure cases requiring salvage therapy with either surgical or other techniques are being reported. Objective. To report the options in treatment of prostate cancer after recurrence or failure of the primary treatment modality. Methods. We report a salvage robotic assisted laparoscopic radical prostatectomy (RALP) for prostate cancer recurrence following high intensity focused ultrasound treatment (HIFU) in the United States. Results. A 67-year-old man who underwent HIFU treatment for prostate adenocarcinoma 2 years prior was presented with a rising prostate specific antigen of 6.1 ng/mL to our clinic. A biopsy proven recurrent disease in the area of previous treatment documented the failure of treatment. The patient elected to undergo a salvage RALP. The operation time was 159 minutes. The patient was discharged from the hospital on postoperative day 1 with no complications. The catheter was removed on post-op day 10. The patient reserved sexual function and urinary continence. The PSA levels on 6 months’ follow-up are undetectable. Conclusions. Salvage RALP is an effective and safe treatment choice for recurrent prostate adenocarcinoma following failed HIFU treatment if operated by an experienced surgeon.